Cash Waqf Auction for The Establishment of Islamic Institution on The Perspective of Islamic Law and Positive Law (A Case Study on Trensains Islamic Institution, Sragen, 2018-2019) - Shalihah, Mar’atus; Cahyo, Eko Nur (AL-IKTISAB: Journal of Islamic Economic Law, 2020)
Waqf (endowment) is one of Islamic philanthropy that offers the basics of justice and benefit. It should be managed with innovative management such as cash and productive waqf that can contribute a positive impact on the socio-economic of society. In the context of waqf fundraising, cash waqf auction is one strategy to accumulate the funding. Cash waqf auctions can be used as a supporting instrument to support and to enhance the general public need and education. Besides, waqf is not limited to the utilization as zakat, therefore the community development programs such as streamlining Islamic school can be carried out through waqf auctions funds. This study is an attempt to clarify the implementation of waqf auction to finance the establishment of an Islamic institution. Then, it discuses the concept and practice of this waqf auction on the perspective of Islamic law and positive law. The methodology used is qualitative research that is using legal sociology and critical legal analysis, data collected through field research, a document study, Â and in-depth interviews. The documents studied were journals, books, papers, and relevant documents for this study. The finding of research reveals that Trensains Islamic Institution is implementing a similar practice of waqf in general. The uniqueness is introducing to the community the development of the waqf system by opening a service office. In the practice of waqf, the Trensain Islamic Boarding School had previously purchased land using bank funds. While the repayment, Treansain auctioned waqf by publishing waqf certificates of 300 per meter and announced using several media. The system of waqf is carried out together. The practice of waqf in Islamic boarding schools is valid according to the provisions of Islamic law. However, based on positive law, they have not met all the requirements. The problem is that the Trensains Islamic Institution should immediately register the nadzir (manager) in the Minister of Religious Affairs and Indonesian Waqf Board.